MEDB-34. A very rare case: medulloblastoma relapse with bone marrow infiltration in a toddler. (3rd June 2022) - Zinke, Claudia; Fleischhack, Gudrun; Hauer, Julia; Lange, Björn Sönke; Dörnemann, Jenny; Hahn, Gabriele; Schackert, Gabriele; Gurtner, Kristin; Meinhardt, Matthias; Jöhrens, Korinna; Knöfler, Ralf
Abstract: We report about a female toddler congenitally deaf and diagnosed with a non-metastatic desmoplastic medulloblastoma (SHH activated, TP53 -wt, variant in LDB1 gene). No tumor predisposition syndrome was found. After complete tumor resection the patient was treated according to I-HIT-MED-Guidance protocol. Five months later an asymptomatic localised relapse (same histology, PTEN frameshift deletion, TERT mutation, LDB1 mutation) detected by routine MRI was treated by complete resection, craniospinal irradiation and an antiangiogenic regimen adapted from the MEMMAT scheme including fenofibrate, thalidomide, celecoxib, topotecan, temozolomide, bevacizumab and intraventricular cytarabine. Before start of systemic treatment blood cell counts were normal. In the second cycle we had to interrupt chemotherapy due to a leukopenia while continuing the antiangiogenic treatment. In order to avoid relevant bone marrow toxicity chemotherapy doses were reduced. Nevertheless we had to stop the fourth cycle because of a severe pancytopenia. Same time the girl presented with fever, neck and leg pain. A full blood count showed: hemoglobin 6.92 g/dl, leukocytes 640/µl, platelets 8, 000/µl. Suspecting an infection supported by the presence of a high CrP value of 230 mg/l the patient was treated with i.v. antibiotics. MRI showed an unspecific retropharyngeal soft tissue augmentation, a pleural effusion and high T2 signals in multiple vertebral bodies but no central tumor relapse. The bone marrow diagnostics revealed a diffuse medulloblastoma cell infiltration with the known PTEN frameshift deletion and LDB1 mutation. The liquor was tumor-cell free. We report on an extremely rare case of an early local relapse of desmoplastic medulloblastoma progressing to a diffuse bone marrow infiltration in a toddler. The girl died due to therapy resistance 9 weeks after bone marrow relapse. It remains unclear whether the fatal course was related to the hereditary deafness syndrome and the molecular alterations of the tumor.